2022
DOI: 10.1017/s1478951522000657
|View full text |Cite
|
Sign up to set email alerts
|

Providing home hospice care for LGBTQ+ patients and caregivers: Perceptions and opinions of hospice interdisciplinary care team providers

Abstract: Objectives Hospice patients and caregivers who are members of sexual and gender minority groups (i.e., LGBTQ+) have reported experiencing unmet needs at end of life (EOL). Negative experiences often stem from challenging interactions with healthcare providers due to ineffective or poor communication and providers’ heteronormative assumptions and biases. Few studies, however, examine hospice care team (HCT) providers’ knowledge, experience, and opinions related to EOL care for LGBTQ+ patients and caregiver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…For example, coworkers and neighbors can offer seemingly small but important support, such as flexibility in scheduling meetings or helping with yard maintenance, that frees up caregiver time and mental load. Research on non-biological/legal family support and the importance of broader social networks in caregiving is limited but growing [ 35 , 36 , 37 ]; future work can elucidate how caregivers can best leverage this support.…”
Section: Discussionmentioning
confidence: 99%
“…For example, coworkers and neighbors can offer seemingly small but important support, such as flexibility in scheduling meetings or helping with yard maintenance, that frees up caregiver time and mental load. Research on non-biological/legal family support and the importance of broader social networks in caregiving is limited but growing [ 35 , 36 , 37 ]; future work can elucidate how caregivers can best leverage this support.…”
Section: Discussionmentioning
confidence: 99%
“…The primary study focused on HCT members’ knowledge and opinions related to LGBTQ+ patient and caregiver EOL care needs. 10 All study procedures were approved by the Institutional Review Board of a large University located in the Intermountain West.…”
Section: Methodsmentioning
confidence: 99%
“…One study by Cloyes and colleagues found that home hospice providers reported LGBTQ + identity as irrelevant to the care provided, not collecting sexual orientation or gender identity (SOGI) regularly, but also reported significant discomfort with providing care to transgender and genderdiverse patients and caregivers. [22] The literature on this topic brings a focus to the tension between collecting SOGI data and how such data is used in the clinical setting-recommending SOGI data could be ideally used for personcentered care to provide equitable transitions for end-of-life care to LGBTQ + patients and caregivers. [22][23][24].…”
Section: Lesbian Gay Bisexual Transgender Queer + (Lgbtq +) Communitymentioning
confidence: 99%
“…[22] The literature on this topic brings a focus to the tension between collecting SOGI data and how such data is used in the clinical setting-recommending SOGI data could be ideally used for personcentered care to provide equitable transitions for end-of-life care to LGBTQ + patients and caregivers. [22][23][24].…”
Section: Lesbian Gay Bisexual Transgender Queer + (Lgbtq +) Communitymentioning
confidence: 99%